Immunophenotypical alterations in a subset of patients with common variable immunodeficiency (CVID). - Baumert, E (1992)
We investigated the expression of surface molecules on lymphocytes from 20 patients with CVID and 40 healthy subjects. Lymphocytes were analysed by dual colour flow cytometry. We identified a subset of patients (8 of 20) characterized by low CD4/CD8 ratio (less than 1.1), expansion of T cells co-expressing the activation marker HLA-DR and significant increase in CD8+ T cells co-expressing CD57. Expression of the adhesion molecules LFA-3 (CD58) and ICAM-1 (CD54) was significantly increased in this subgroup. In addition, within the CD4+ T cells the percentage of CD29+ (memory) cells was increased, while the CD45RA and LAM-1 (Leu-8) antigens were depressed. These results indicate that in a subgroup of CVID patients T cells are activated in vivo and the CD57+CD8+ lymphocyte subpopulation, supposed to comprise functional suppressor T cells, is expanded. We suggest a chronic viral infection in these patients, but it is not clear whether this is primary or secondary to the underlying defect.